Apparent digestibility and nutritional status of capuchin monkeys (Sapajus sp.) under human care - Silva, Maira Beatriz Gandolfi [UNESP]; Tokashiki, Erick Yuji [UNESP]; Testa, Carolyne Assis Eigenheer Pinke [UNESP]; de Lima Meirelles, Paulo Roberto [UNESP]; Okamoto, Priscylla Tatiana Chalfun Guimarães [UNESP]; Urrego, Ana Camila Beltrán [UNESP]; Melchert, Alessandra [UNESP] (Wiley, 2024)
Background: Studing the nutritional needs and dietary habits of primates is essential to ensure their health and well-being. This includes the understanding of the use of nutrients and its correlation with health parameters. Methods: Diet and nutritional parameters of 13 captive capuchin monkeys (Sapajus sp.) were assesed. Apparent digestibility of dry matter and nutrients were evaluated. Nutritional status was established based on body condition score (BCS) and muscle mass score (MMS). Results: High apparent digestibility coefficients (ADC) were observed for crude protein and ether extract, but low for minerals and crude fiber. The ADC of EE and CF were related to MMS, and the biochemical parameters did not correlate with the AD coefficients obtained in the group. The nutritional status of the animals remained inadequate in 84.6% of the individuals, suggesting a reformulation of the diet and nutritional management.
Keywords: digestion; food intake; nutrition; primates